Mechanical properties of injection moulded 316L stainless steels with (TiC) N additions - (:unkn) unknown (MANEY PUBLISHING, 2007)
The present study compares the effect of TiC and TiCN additions on the densification and mechanical properties response of injection moulded 316L stainless steels. The sintered density of straight as well as TiC and TiCN reinforced injection moulded 316L stainless steels increases with increasing sintering temperature. The addition of TiC and TiCN improves the hardness and wear resistance with increasing sintering temperature.
Keywords: powder injection moulding; 316L stainless steel powder; TiC; TiCN; mechanical properties; MATRIX COMPOSITES; CARBIDE; POWDER